Results of an adult weight-management program and reflections as the influence of weight on quality of life in patients with obesity: THE INFLUENCE OF WEIGHT MANAGEMENT PROGRAM ON QUALITY OF LIFE IN PATIENTS WITH OBESITY - Ongan, Dilek; Kuş, Aynur Demir; Ongan, Emre; Kılıç, Demet (Progress in Nutrition, 2019)
Background and aim: Recent studies focus on obesity treatment programs that aim at holistically improving metabolic, physical, psychological and social health. This study was conducted to elucidate the results of a hospital-based adult weight-management program in terms of health status and its reflections as the influence of weight on quality of life (QoL) in patients with obesity. Methods: This cross-sectional analytical study was conducted with adult (aged>18 y) patients with obesity (Body Mass Index≥30.0 kg/m2) (n=73) in Outpatient Clinic for Obesity of Çiğli Regional Education Hospital in İzmir/Turkey. Socio-demographic data were collected through face-to-face interviews. Anthropometric measurements (body weight, height, waist&hip circumferences) were taken. Biochemical findings (fasting blood glucose, HbA1c, insulin, blood lipids) were obtained from patient files. Individualized weight loss program was planned by the dietitian. The influence of weight on QoL was determined with Obesity and Weight-Loss Quality-of-Life (OWLQOL) scale. Results: Mean age was 42.3±10.3 years; 87.7% were women. Comorbidities were hypertension (23.3%), hyperlipidaemia (19.2%), diabetes mellitus (12.3%). Significant decreases from baseline to post-treatment were found in weight loss (9.55±3.21%), BMI, waist and hip circumferences, waist-to-hip ratio, waist-to-height ratio and body fat percentage. Post-treatment levels of fasting blood glucose, insulin, total cholesterol, HDL and LDL-cholesterol were significantly lower compared to baseline. The OWLQOL score significantly decreased showing less negative influence of weight on QoL. Conclusions: This conventional hospital-based weight management program provided reduction in body weight at desired levels, improved metabolic indicators for comorbidities and resulted in improvement in QoL.